PERSEPSI KERENTANAN DAN HAMBATAN IBU TERHADAP PENDIDIKAN SEKSUAL PADA ANAK USIA DINI (4-6 TAHUN) - Debby Ulina Fatmawati; Syamsulhuda BM; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Sexual violence in children is the practice of sexual intercourse committed by violent means to a child. Semarang is the region with the highest violence in Central Java. This is evidenced by the decrease in the number of complaints in 2015 to 2016, and increase in 2017. This happens because sexual violence is an event like an iceberg. Sexual violence in children can be minimized with early sexual education. The existence of a taboo perception by mother about sexuality causes the mother to hesitate to perform the action. However, in this study can be seen perceptions of vulnerability and barriers experienced by mothers related to sexual education. The subjects were 8 people with purposive sampling method and data collection technique with in-depth interview. From the results of the study, the subject of research has conducted sexual education because it senses the existence of vulnerability to the child's condition that comes from the self in the children, the environment, and the negative impact of technology. However, the perceived barriers that research subjects are also one of the factors that make the research subject to hesitate to perform consistent sexual education.